Why do cognitive prompts hurt learning in older adults?. (12th January 2020) - Kraiger, Kurt; Cavanagh, Thomas M.; Willis, Colin M. G.
Abstract : The purposes of the present investigation were to attempt to replicate the negative effects for learning prompts in older adults reported by Cavanagh, Kraiger and Peters (2016), determine if the impact of learning prompts depends on type of prompt, and investigate the two possible explanations of the negative impact of prompts – increased cognitive load and higher negative affect. Learning prompts refer to short text inserted into training content to encourage trainees to rehearse new content or engage in meta‐cognitive activity. Although learning prompts generally lead to greater learning in training, Cavanagh et al. reported a negative impact for prompts on measures of recall and transfer. Using similar training materials and learning outcome measures, we conducted two studies using both elaboration and meta‐cognitive prompts in online training. In the first, older adults ( N  = 194) between 55 and 70 years and younger adults ( N  = 218) were randomly assigned to either a meta‐cognitive, elaboration or no prompts (control) condition. Older adults learned less and reported greater mental effort than younger learners, but these effects were not moderated by prompt condition. In the second, N  = 57 older adults were randomly assigned to the same three prompts conditions listed above. Older adults learned less with prompts than without, but there were no differences between conditions in mental effort or negative affect. In sum, we found negative effects for learning prompts in older adults in two studies, but found no evidence to suggest that these effects were due to either increased cognitive load or greater negative affect.